Continuous and discrete signals and systems - Soliman, Samir S.; Srinath, Mandyam D. (Upper Saddle River, N.J. : Prentice-Hall, 1998)
Representing signals. Continuous-time systems. Fourier series. The fourier transform. The laplace transform. Discrete-time systems. Fourier analysis of discrete-time systems. The Z-transform. The discrete fourier transform. Design of analog and digital filters.
Keywords: Telecommunication systems; Signal processing; Signal theory; Signal theory (Telecommunication); Signal processing -- Mathematics; Transformations (Mathematics); System analysis